A JURIDICAL ANALYSIS OF THE IMPLEMENTATION OF NATIONAL POLICE CHIEF REGULATION NUMBER 9 OF 2017 REGARDING THE PROHIBITION ON CONCURRENT POSITIONS HELD BY NATIONAL POLICE MEMBERS AS COMMISSIONERS OF PAYMENT SERVICE PROVIDER COMPANIES - Faujiah Faujiah; MS Tumanggor (Jurnal Ikhtibar Nusantara, 2026)
This article aims to analyze the legal implications and potential conflicts of interest regarding dual identity or role alignment when an active police officer, specifically the Head of Sub-Directorate for Fiscal, Monetary, and Foreign Exchange (Kasubdit Fismondev) of DITRESKRIMSUS Polda Kalteng, serves as a commissioner in a Payment Service Provider (PJP) company. The analysis strictly evaluates this phenomenon against the Chief of Indonesian National Police Regulation (Perkap) No. 9 of 2017 concerning Business Operations by Members of the Indonesian National Police. Using a normative juridical research method with conceptual, statutory, and analytical approaches, this study examines the clear structural overlap between law enforcement powers and private commercial operations. The findings indicate that such positioning violates Article 2 Paragraph (2) Letter c regarding power-scope business restrictions and Article 3 concerning the abuse of official authority. The study concludes that stricter enforcement by the Internal Affairs Division (Bid Propam) through the Business Assessment Team mechanism is legally compulsory to prevent structural conflicts of interest.